In Sardinia : an unexpected journey in Italy - Biggers, Jeff, 1963- (Melville House, 2023)
"After three decades of living and traveling in Italy, Jeff Biggers finally crossed over to Sardinia, uncovering a treasury of stories amid major archaeological discoveries rewriting the history of the Mediterranean. Based in the bewitching port of Alghero, guided through the island's rich and largely untranslated literature, he embarked on a rare journey around the island to experience its famed cuisine, wine, traditional rituals and thriving cultural movements. Beyond its fabled beaches, reconsidering how its unique history and ways have shaped Italy and Europe today, Biggers explores how travelers must first understand Sardinia and its ancient and modern history to truly understand the rest of Italy"--